2022
DOI: 10.1152/ajpcell.00320.2021
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 and Notch3 coordinate for pericyte-induced stabilization of vasculature

Abstract: The Notch pathway regulates complex patterning events in many species and is critical for the proper formation and function of the vasculature. Despite this importance, how the various components of the Notch pathway work in concert is still not well understood. For example, NOTCH1 stabilizes homotypic endothelial junctions, but the role of NOTCH1 in heterotypic interactions is not entirely clear. NOTCH3, on the other hand, is essential for heterotypic interactions of pericytes with the endothelium, but how NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 59 publications
3
26
0
Order By: Relevance
“…Notch1 expression was increased at 2 weeks postirradiation. It is worth noting that by performing single-cell RNA-seq analysis of brain tissues from RIBI patients (Figure S4C), we confirmed that Notch3 expression was most abundant in the mural cells (including VSMCs and pericytes), as previously reported, 27 and less detected in the endothelial cells. We next used Pdgfrb -Cre; Ai9 mice to verified the specific expression of Notch3 in the tdTomato-positive mural cells in the brains of irradiated and control mice (Figure 4C).…”
Section: Resultssupporting
confidence: 88%
“…Notch1 expression was increased at 2 weeks postirradiation. It is worth noting that by performing single-cell RNA-seq analysis of brain tissues from RIBI patients (Figure S4C), we confirmed that Notch3 expression was most abundant in the mural cells (including VSMCs and pericytes), as previously reported, 27 and less detected in the endothelial cells. We next used Pdgfrb -Cre; Ai9 mice to verified the specific expression of Notch3 in the tdTomato-positive mural cells in the brains of irradiated and control mice (Figure 4C).…”
Section: Resultssupporting
confidence: 88%
“…The contemporary increase of Jag1 and LFng that is induced by Bmp9, together with the anti-angiogenic role of Bmp9, thus appear counterintuitive. Jag1 plays a crucial role for the signaling crosstalk of ECs with pericytes (Liu, Kennard and Lilly, 2009; Tefft et al ., 2022), fundamental for endothelial stabilization (Geevarghese and Herman, 2014; Dibble et al ., 2023). Therefore, to reconcile Bmp9-mediated LFng and Jag1 upregulation, we investigated whether LFng plays a role in this context.…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by previous experiments (Benedito et al ., 2009; Larrivée et al ., 2012; Kakuda and Haltiwanger, 2017; Kakuda et al ., 2020; Tefft et al ., 2022), we extended our ODE model of EC signaling by adding the EC crosstalk with pericytes as mediated by Jag1 (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Differences in the role of pericytes on barrier function in these microvessels may result from differences in cell sources, seeding arrangements, shear stress magnitude, and lumen diameter. Recently, Tefft et al (47) used a microvessel model with human brain vascular pericytes and human neonatal dermal blood microvascular ECs to investigate the signaling pathways involved with pericyte stabilization of the endothelium. Pericyte NOTCH3 and EC NOTCH1 played critical roles in forming stable EC junctions.…”
Section: :1 E220021mentioning
confidence: 99%
“…Recently, Tefft et al . ( 47 ) used a microvessel model with human brain vascular pericytes and human neonatal dermal blood microvascular ECs to investigate the signaling pathways involved with pericyte stabilization of the endothelium. Pericyte NOTCH3 and EC NOTCH1 played critical roles in forming stable EC junctions.…”
Section: Engineered Microvesselsmentioning
confidence: 99%